Chronotype, circadian rhythm, and psychiatric disorders: Recent evidence and potential mechanisms - Zou, Haowen; Zhou, Hongliang; Yan, Rui; Yao, Zhijian; Lu, Qing (Frontiers in Neuroscience, 2022)
Abstract: The circadian rhythm is crucial for physiological and behavioural functions. Chronotype, which represents individual preferences for activity and performance, is associated with human health issues, particularly psychiatric disorders. This narrative review, which focuses on the relationship between chronotype and mental disorders, provides an insight into the potential mechanism. Recent evidence indicates that (1) the evening chronotype is a risk factor for depressive disorders and substance use disorders, whereas the morning chronotype is a protective factor. (2) Evening chronotype individuals with bipolar disorders tend to have more severe symptoms and comorbidities. (3) The evening chronotype is only related to anxiety symptoms. (4) Although increasing evidence has emerged, the relationship between chronotype and schizophrenia remains unclear. (5) The evening chronotype is significantly associated with eating disorders, while the majority of studies have focused on binge eating disorders. Furthermore, the underlying mechanisms or influence factors are described in detail, including clock genes, brain characteristics, neuroendocrinology, the light/dark cycle, social factors, psychological factors, and sleep disorders. These findings provide the latest evidence on chronotypes and psychiatric disorders and serve as a valuable reference for researchers.